Advances in the Clinical Application of Novel PCSK9 Inhibitors for High-Risk Atherosclerotic Cardiovascular Disease - Yujie Fang (International Journal of Biology and Life Sciences, 2026)
Dyslipidemia is a major contributor to atherosclerotic cardiovascular disease (ASCVD), the leading cause of morbidity and mortality worldwide. Proprotein convertase subtilisin/kexin type 9 (PCSK9) promotes hepatic low-density lipoprotein receptor (LDLR) degradation, elevating plasma low-density lipoprotein cholesterol (LDL-C) and contributing to plaque initiation, progression, and destabilization via lipid-dependent and -independent pathways (e.g., inflammation, endothelial dysfunction, thrombosis). PCSK9 inhibition is a validated target for intensive lipid management Beyond statins, monoclonal antibodies (evolocumab, alirocumab) and siRNA-based therapy (inclisiran) achieve reductions in LDL-C of >50%. Large outcome trials (FOURIER, ODYSSEY OUTCOMES, ORION series) have demonstrated reduced major adverse cardiovascular events (MACE) and favorable safety in high-risk populations including acute coronary syndrome, familial hypercholesterolemia, and statin intolerance. Newer approaches include oral small molecule inhibitors (e.g., MK-0616, AZD0780), therapeutic vaccines (e.g., AT04A), and gene-editing (e.g., VERVE-101) with improved adherence, durability or potential cure. For patients with very-high-risk or high-risk ASCVD who do not achieve LDL-C targets with traditional therapies, clinical guidelines, including China-specific recommendations, support the use of PCSK9 inhibitors to lower LDL-C and further reduce CV risk.